«Tutto parla in termini sessuali»: educazione sessuale, adolescenza e verginità in "Domani è troppo tardi" (1950) (Schermi. Storie e culture del cinema e dei media in Italia, 2022)
This paper analyzes the debate on sexual education emerged in the Italian press following the release of the film “Domani è troppo tardi” (Léonide Moguy, 1950). In Post-War Italy, the theme of sexual knowledge occupies the public discourse, with an emphasis on the control of female sexuality and the affirmation of virginity. Even the iconographic and textual representations of the main character, the sixteen-year-old Anna Maria Pierangeli, trace the stereotypes of virtue and female sacrifice, in line with a traditional morality and the Catholic conception of femininity. The intense debate catalyzed by the film describes adolescence as a hybrid territory: an asphyxiating place characterized by precepts, opinions, clinical observations, and control schemes; but also a transitional stage stimulated by the new sexualization of the cultural industry.